2021
DOI: 10.37934/jrnn.1.1.5361
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Mediated Production and Characterisation of Magnetic Nanoparticles Using Fruit Peel Extract

Abstract: The overwhelming request for nanodevices and heat flow developments has led to consider magnetic Fe3O4 nanoparticles as a new dawn to the sophisticated nanotechnology in a sustainable manner. This research presented a facile production of Fe3O4 nanoparticles using co-precipitation method and the extract of Garcinia Mangostana fruit peel waste as a green stabilizer and capping agent. The X-ray powder diffraction (XRD) planes of the synthesized nanoparticles showed the formation of magnetite Fe3O4 nanoparticles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…It is also worth mentioning that several studies have used plant-based stabilizer/capping agents in the green synthesis methods of MNPs. [103][104][105][106]…”
Section: Biosynthesis Methodsmentioning
confidence: 99%
“…It is also worth mentioning that several studies have used plant-based stabilizer/capping agents in the green synthesis methods of MNPs. [103][104][105][106]…”
Section: Biosynthesis Methodsmentioning
confidence: 99%
“…This was probably due to the effects of Brownian motion, whereby the nanoparticles were agitated randomly due to the increased fluid velocity around them. Brownian motion is the intercollision between nanoparticles and their surroundings, represented in this case by the base fluids and microchannel walls [60]. Higher flow rates elevated the inertial force in the fluid, leading to vigorous nanoparticle movement within the fluid.…”
Section: Mchs Heat Transfer Coefficient and Nusselt Numbermentioning
confidence: 99%
“…Nanoparticles have high stability and a long storage time. In another publication by this group of scientists, they demonstrated that the extract of Garcinia Mangostana fruit peel could be used as a bio-stabilizer and capping agent to enhance physicochemical properties and stability of Fe 3 O 4 nanofluid [8].…”
Section: Green Synthesis Of Hybrid Magnetic-semiconductor Oxides Nano...mentioning
confidence: 99%